2021
DOI: 10.46483/deuhfed.882663
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Women’s Personality Traits on Traumatic Birth Perception

Abstract: ÖzGiriş: Kadın yaşamında eşsiz bir deneyim olan doğum genellikle olumlu bir olay olarak algılanmaktadır. Amaç: Bu çalışma 18-65 yaş arasındaki kadınların kişilik özelliklerinin travmatik doğum algısına etkisini belirlemek amacıyla yapıldı. Yöntem: Kesitsel tanımlayıcı ve ilişki arayıcı tipteki çalışmanın evrenini Türkiye'de yaşayan 18-65 yaş aralığındaki kadınlar, örneklemini ise İstanbul'da yaşayan, Türkçe dilini okuyup anlayabilen ve çalışmaya katılımda gönüllü 300 kadın oluşturdu. Veri toplama aracı olarak … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 32 publications
1
5
0
Order By: Relevance
“…Still, the difference among the groups was not statistically significant (p>0.05, Table 1). Likewise, as in the reports of other studies in the literature, although the differences were statistically insignificant, it was found that the non-working mothers had higher traumatic childbirth perception levels than the working mothers (Yılmaz et al, 2021), and higher numbers of pregnancies and a history of stillbirth or miscarriage (Şahin, 2020) increased their mean PTCS scores. In this study, the mean PTCS score of the mothers who had curettage in their obstetric history was found significantly higher than the mean score of those with no curettage in their obstetric history (p<0.05, Table 1).…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…Still, the difference among the groups was not statistically significant (p>0.05, Table 1). Likewise, as in the reports of other studies in the literature, although the differences were statistically insignificant, it was found that the non-working mothers had higher traumatic childbirth perception levels than the working mothers (Yılmaz et al, 2021), and higher numbers of pregnancies and a history of stillbirth or miscarriage (Şahin, 2020) increased their mean PTCS scores. In this study, the mean PTCS score of the mothers who had curettage in their obstetric history was found significantly higher than the mean score of those with no curettage in their obstetric history (p<0.05, Table 1).…”
Section: Discussionsupporting
confidence: 75%
“…Similarly, several studies in the literature have reported significant relationships between age and traumatic childbirth perceptions. Yılmaz et al (2021) determined higher levels of traumatic childbirth perceptions among individuals under the age of 40 (Yılmaz et al, 2021). The relationship between education levels and traumatic childbirth perceptions has not been completely clarified yet.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Women's perceptions of childbirth and the meaning they attribute to delivery may differ according to personal characteristics and cultural values (27,28). Görgün (29) reported that although there was no statistically significant difference between the groups, the total mean score of the traumatic childbirth perceptions of pregnant women living in cities was higher than those living in rural areas (29).…”
Section: Discussionmentioning
confidence: 99%
“…Ordu University J Nurs Stud 2022, 6(2), 273-280 DOI:10.38108/ouhcd.1093849 had a moderate traumatic birth perception, supporting the results of our study. The mean TBPS scores reported in some of these studies, namely the studies of Bay and Sayıner (2021), Aktaş (2018) and Yalnız Dilcen et al, (2022), were 63.45±28.116, 70.57±1.89, and 61.22±14.55, respectively. Additionally, in the study of Yılmaz Et al. (2021), the total score of TBPS was found as 64.57 ± 31.48 (Yılmaz et al, 2021).…”
Section: Traumatic Birth Perception In Women Of Reproductive Agementioning
confidence: 97%